Asymmetric Information and Information Assimiliation - Yulianto, Arief; ., Widiyanto; Witiastuti, Rini Setyo; Plangsorn, Boonrat (Journal of Ecohumanism, 2024)
The purpose of this research is to determine the impact of information assimilation on equity issuance in the banking sector. The data consists of 384 observations of banking and finance companies listed on the Indonesian Stock Exchange from 2020 to 2023. A univariate analysis was utilized to identify the differences in asymmetry between companies with seasoned equity offerings (SEOs) and non-SEOs to meet capital requirements in the banking sector. The research indicates that SEO and non-SEO banks exhibit significant differences in their spreads. Despite the banking sector’s access to deposits and wholesale funding to finance capital shortages or prospective projects, equity issuance by the banking sector has increased. The presence of regulations on information disclosure does not produce asymmetric information; however, the increased spread among companies with SEOs is due to the more complex information assimilation process, which in turn results in a wider spread relative to the fundamental price.